Thermoelectric generators versus photovoltaic solar panels: Power and cost analysis - A. Marzouk, Osama (Edelweiss Applied Science and Technology, 2024)
In the current study, the concept of building a power plant using thermoelectric generator (TEG) modules is investigated, both technically and economically. The hypothesized thermoelectric generation power plant is a modular system, consisting of a large array of electrically connected thermoelectric generator units for generating clean electricity with-out greenhouse gas (GHG) emissions, noise, or hazardous solid wastes. The envisioned thermoelectric generation power plant (TEGPP) considered here is assumed to utilize solar radiation as a heat source, and water as a heat sink. The viability of such a concept is examined in the current study based on available specifications of a high-output thermo-electric generator module released in the market (TEG1-24111-6.0). Benchmarking is car-ried out considering a high-efficiency photovoltaic (PV) panel in the market (SunPower SPR-MAX3-400), assuming that it operates under standard solar radiation of 1,000 W, and with a standard panel temperature of 25 C, causing it to give an output electric power of 400 W (DC or direct current). It is found that in order to have an electric power of a thermoelectric generator unit similar to that of a photovoltaic panel of equal surface area, the temperature at the hot side of the thermoelectric generator unit should be about 70 C if the cold-side temperature is 30 C. However; under this output power equiva-lence, the price of the thermoelectric generator unit is about 90 times that of a photovol-taic panel of equal size (based on prices of October 2023). At an elevated hot-side tem-perature of 300 C for the thermoelectric generator unit (with the cold-side temperature being still 30 C), the thermoelectric generator unit can generate electric power that is about 25 times the power generated by a photovoltaic panel of an equal geometric area. This big boost in the output power still does not counteract the large cost difference be-tween the thermoelectric generator technology and the photovoltaic technology, where the per-watt(electric) cost in the case of thermoelectric generators is 3.5 times its value in the case of photovoltaic panels. Thus, the TEG technology in its intensified generation mode is still relatively more expensive compared to the PV technology. The practical im-plications of the current study are excluding the thermoelectric generation (based on the Seebeck effect) concept from large-scale commercial power plants, and viewing thermoe-lectric generators as sources of small electric power for waste heat management or con-venient power sources for small mobile devices.